Prevalencia de fragilidad en una población urbana de mayores de 65 años y su relación con comorbilidad y discapacidad - Castell Alcalá, María Victoria (Aten Primaria, 2010)
AIM: To estimate prevalence of frailty, by Fried criteria, in a Spanish urban old population, and to analyse relationship with comorbidity and disability. POPULATION: Aged ≥65 living in Peñagrande area (Fuencarral district in Madrid, Spain). DESIGN: Cross-sectional study. Baseline evaluation of "Cohort of Peñagrande" established in 814 person. MEASUREMENTS: Frailty was defined by the presence of ≥3 of the following criteria: unintentional weight loss, weakness (grip strength), exhaustion, low walking speed, and low physical activity. Age, gender, marital status, educational level, global income at home, comorbidity and disability were measured. A descriptive bivariate and multivariate analysis was performed and ponderated by age and gender in study population. Association was estimated by Odds Ratio and confidence intervals (OR, IC 95%). RESULTS: 73,3% participated (N=814), 48,6% were men and the median age was 76 [71 – 83]. The estimated prevalence of frailty in the study population was 10,3% (IC95%: 8,2 – 12,5): 8,1% male and 11,9% female (p=0.084). Frailty was associated with aged ≥85 (OR=3,61; IC95%: 1,26 – 10,29), low educational level (OR=1,71; IC95%: 1,01 – 2,90), comorbidity (OR=1,27; IC95%:1,03 – 1,56 by each process) and disability (OR=15,61; IC95%: 8,88 – 27,45). CONCLUSIONS: Prevalence of frailty in an elderly spanish population is similar to international studies. In our environment first beneficiary population for frailty detection is constituted by people aged ≥85, and those with comorbidity and low educational level.